Epsilon-Near-Zero Substrate Engineering for Ultrathin-Film Perfect Absorbers - Rensberg, Jura; Zhou, You; Richter, Steffen; Wan, Chenghao; Zhang, Shuyan; Schoppe, Philipp; Schmidt-Grund, Rdiger; Ramanathan, Shriram; Capasso, Federico; Kats, Mikhail A.; Ronning, Carsten (Physical Review Applied, 2017)
Efficient suppression of reflection is a key requirement for perfect absorption of light. Recently, it has been shown that reflection can be effectively suppressed utilizing a single ultrathin film deposited on metals or polar materials featuring phonon resonances. The wavelength at which reflection can be fully suppressed is primarily determined by the nature of these substrates and is pinned to particular values near plasma or phonon resonances - the former typically in the ultraviolet or visible and the latter in the infrared. Here, we explicitly identify the required optical properties of films and substrates for the design of absorbing antireflection coatings based on ultrathin films. We find that completely suppressed reflection using films with thicknesses much smaller than the wavelength of light occurs within a spectral region where the real part of the refractive index of the substrate is n1, which is characteristic of materials with permittivity close to zero. We experimentally verify this condition by using an ultrathin vanadium dioxide film with dynamically tunable optical properties on several epsilon-near-zero materials, including aluminum-doped zinc oxide. By tailoring the plasma frequency of the aluminum-doped zinc oxide, we are able to tune the epsilon-near-zero point, thus achieving suppressed reflection and near-perfect absorption at wavelengths that continuously span the near-infrared and long-wave midinfrared ranges.
CRIS-Team Scopus Importer:2023-04-20